From skin testing to molecular diagnostics: the precision leap in dust mite allergy diagnosis and clinical translation challenges - Han, Ming; Luo, Jindan; Zhou, Wenjing; Wen, Shuhui; Zhou, Yi; Ye, Yanjuan; Ge, Xiaoli (Frontiers in Allergy, 2025)
Dust mites are ubiquitous in human living environments and represent the primary source of indoor air allergens worldwide. They are capable of triggering allergic rhinitis, conjunctivitis, asthma, atopic dermatitis, and other allergic conditions. Long-term avoidance of dust mite allergens should decrease sensitization, significantly improves skin lesions, and reduces both the development and severity of respiratory diseases. Therefore, early diagnosis of dust mite allergy is critical for effective treatment and intervention. This review summarizes the existing methods for detecting dust mite allergy, which include both in vivo and in vitro approaches—such as skin prick testing(SPT), atopy patch testing(APT), provocation tests, basophil activation test (BAT), and molecular component-resolved diagnostics(CRD)—and analyzes the underlying principles, advantages, and limitations of each method to serve as a reference for the development of future detection methods.